Insulin Resistance and Biological Aging: The Role of Body Mass, Waist Circumference, and Inflammation. (9th May 2022) - Tucker, Larry A.
Abstract : The purpose of this investigation was to evaluate the association between insulin resistance and biological aging in a randomly selected sample of 2, 596 U.S. women and men. Another key objective was to examine the extent to which the insulin resistance and biological aging association was influenced by differences in body mass, waist circumference, and systemic inflammation. Biological aging was indexed using the length of leukocyte telomeres. The homeostatic model assessment (HOMA) was employed to index insulin resistance. The body mass index (BMI) was used to represent body mass independent of height. Waist circumference was used to assess abdominal adiposity, and C-reactive protein (CRP) was measured to index body-wide inflammation. Insulin resistance and telomere length were both treated as continuous variables. Results revealed that insulin resistance was related significantly with cellular aging, after adjusting for several demographic covariates (F = 5.7, P = 0.0234 ). The association remained significant after controlling for multiple demographic and lifestyle covariates together (F = 4.6, P = 0.0410 ). However, after controlling for BMI, along with the other covariates, insulin resistance was no longer associated with biological aging F = 2.1, P = 0.1573 . After adjusting for differences in waist circumference, along with the demographic and lifestyle covariates, but not BMI, the relationship between insulin resistance and biological aging was negated further F = 1.5, P = 0.2283 . Adjusting for CRP with the demographic and lifestyle covariates, but not BMI or waist circumference, weakened the relationship (F = 4.0, P = 0.0552 ). Evidently, if all adults in the U.S. had the same BMI or waist circumference, there would not be a relationship between insulin resistance and telomere length. It appears that insulin resistance accounts for differences in biological aging mainly because of differences in BMI and waist circumference, especially the latter.